Whole Exome Sequencing Identified Novel ARMC9 Variations in Two Cases With Joubert Syndrome - Wang, Hao; Luo, Guanjun; Hu, Wensheng; Mei, Jin; Shen, Yue; Wang, Min; Tan, Yuan; Yang, Yang; Lu, Chao; Zhao, Yong; Qi, Ming (Frontiers in Genetics, 2022)
Background: Biallelic variations in armadillo repeat-containing 9 (ARMC9) gene was recently defined to cause Joubert syndrome (JS) type thirty. In this study, two cases with probands displaying typical indications of JS were enrolled and underwent a series of clinical and genetic investigations. Methods: Routine evaluation including magnetic resonance imaging (MRI) was carried out. And, whole-exome sequencing (WES) was performed on the probands to detect causative variants. Next, in silico structural and molecular dynamics (MD) analysis was conducted on the novel missense variant for analyzing its intramolecular impact. Meanwhile, an in vitro study with minigene system was performed to explore the specific impact on mRNA splicing of another variant. Results: Both patients exhibited typical JS presentations, such as the "molar tooth sign". WES identified diagnostic variations in both probands, which included two novel variants, namely ARMC9: c.1027C>T (p.R343C) and c.1878+1G>A. In silico analysis indicated the c.1027C>T (p.R343C) would likely affect the secondary structure of ARMC9 protein. Minigene study demonstrated that c.1878+1G>A would cause an 18bp insertion downstream of exon 20, which probably leads to a 6-residue redundancy in the peptide. Conclusion: The findings in this study expanded the mutation spectrum of ARMC9 associated JS, and are conducive to the understanding of the functional importance of ARMC9 in primary cilia development.